Exploring Lecturers’ Perceptions of Developing Web 2.0 Extensive Listening Materials using the ICE Framework - Milarisa , Surti; Bayu, Muhammad; Ganie, Djupiansyah; Mawi, Tiarasari; Djamal, Merlin (REiLA : Journal of Research and Innovation in Language, 2025)
Extensive listening has long been acknowledged as an essential skill in second language acquisition, yet its implementation in higher education often suffers from limited frameworks that fail to integrate technology, cultural relevance, and learner autonomy. While prior research has highlighted the potential of Web 2.0 technologies in fostering collaboration and authentic engagement, few studies have investigated how lecturers perceive the integration of structured listening frameworks into this digital landscape. This study addresses this gap by examining lecturers’ perceptions of developing Web 2.0-based extensive listening materials through the Interesting, Comprehensible, and Enjoyable (ICE) Framework. Using a descriptive qualitative design supported by quantitative insights, data were collected from 42 English lecturers across nine universities in five Indonesian provinces through online questionnaires and semi-structured interviews. The findings indicate that lecturers regarded the ICE framework as engaging, pedagogically relevant, and highly supportive of listening instruction. The “Interesting” dimension was affirmed through authentic and culturally embedded materials, notably Berau folklore; the “Comprehensible” component was reflected in accessible vocabulary and structured content; and the “Enjoyable” element enhanced learner autonomy, motivation, and reduced listening difficulties. These results suggest that the ICE Framework not only advances the design of Web 2.0 listening materials but also promotes a more student-centered and culturally responsive pedagogy. By positioning listening instruction at the intersection of technology, pedagogy, and cultural relevance, this study provides a valuable contribution for researchers seeking theoretical refinement and practitioners aiming for practical innovation in English language teaching.